(untitled) (American & British Studies Annual, 2015)
This article discusses the opposition of knowledge and ignorance in Kazuo Ishiguro’s Never Let Me Go and Graham Swift’s Shuttlecock. While the protagonists of both novels seek knowledge, the value of knowledge is ultimately challenged. The article argues that, despite their tendency to show the pitfalls of insufficient knowledge in their stories, in these two novels Ishiguro and Shift make a case for the ethical benefits of ignorance.